Espectroscopia Raman na L-valina deuterada a baixas temperaturas - Barboza, Felipe Moreira (2012)
Deuteration allows the identification of several species of vibrations, through the comparison of vibrational spectra of the deutered and hydrogeneted samples. In this work we base studied the vibrational properties of L-valine-d8 (99,8 % atom % D) through the Raman spectroscopy technique. At first, the assignment of all Raman active vibratonal mades of L-valine was revisited, and a comparison with a previous work was done. In particular, several bands associated to stretching of NH_3^+ and stretching of CH3, among others, which are observed in the interval 2000 – 2400 cm-1 were assigned. In the second part of the work, again using Raman spectroscopy, it was studied the vibrational modes of the crystal in the temperature range 100 – 300 K. It is known from literature that hydrogenated L-valine undergoes a phase transition at about 110 K. It also known that in deuterated crystals hydrogen bands - through Ubbehlode effect – tend to be less strange and, as a consequence, a comparative analyses between the deuterated and hydrogenated samples is very important. In a previous work on L-alanine it was observed that deutaration induces a new phase at low temperatures. In the investigation on L-valine, at least in the temperature range studied, it was not possible to note any change in the Raman spectra which could be associated to a structural phase transition. Both in the external modes region any great change is verified. As a consequence, we can infer that L-valine-d8 is stable between 100 and 300 K. A discussion about the difference behaviors at low temperatures of L-valine and L-alanine (both deuterated and hydrogenated) is also furnished in the present work.